The effect of hot water bag, effleurage massage and routine care on the intensity of active labor pain in primiparous women- A randomized clinical trial study - Zahra Kohzad; Shahnaz Golian Tehrani; Azadeh Hosseinkhani; Fatemeh Bayat; Mahnaz Keshavarz Afshar (Mashhad University of Medical Sciences, 2023)
Introduction: Pain is a common phenomenon and an inevitable part of the childbirth process, and the effective control of this pain, like other acute pains, is an important issue for society and health. Many studies show that one of the main reasons for not choosing natural childbirth by mothers is the fear of natural labor and childbirth pain. The present study was performed with aim to compare the effect of effleurage massage and hot water bag in reducing the pain of the first stage of labor for primiparous women. Methods: This randomized clinical trial study with a control group was performed in 2015-2016 on 90 primiparous pregnant women admitted to the gynecology hospital of Tehran. The samples were randomly assigned to two intervention groups and one control group. The intervention group 1 received 15 minutes of massage, and in the intervention group 2, a hot water bag was placed in the back area in three times at dilatation 4, 6 and 8 cm for 15 minutes and the control group received routine care in the delivery room. In all three groups, pain intensity was measured using the VAS scale until the end of labor. Data were analyzed using SPSS software (version 24) and T-test, Chi-square, Fisher and analysis of variance with repeated measures. P<0.05 was considered statistically significant. Results: After the intervention, the pain intensity significantly reduced in the intervention groups at the beginning of the active and transition phase of childbirth compared to the control group (p<0.001). However, there was no significant difference between the two intervention groups in the amount of pain reduction (p>0.001). Conclusion: In this study, both the use of hot water bag and massage therapy were effective in reducing pain during labor. Therefore, these interventions can be performed by midwives in care and treatment centers to make childbirth pleasant and improve the quality of mother and baby care.